2017
DOI: 10.1155/2017/6904325
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interleukin-17, Interleukin-23, and Transforming Growth Factor-β in Pregnancy Complicated by Placental Insufficiency

Abstract: Aim The aim of the study was to evaluate the role of Interleukin-17 (IL-17), Interleukin-23 (IL-23), and transforming growth factor-β (TGF-β) in pregnancy complicated by placental insufficiency and in normal pregnancy. Material and Methods The study comprised 34 patients with pregnancy complicated by fetal growth restriction (FGR) associated with preeclampsia (PE), as well as 35 healthy pregnant women. The concentrations of IL-17, IL-23, and TGF-β in sera from maternal peripheral blood were determined by an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 34 publications
8
26
0
Order By: Relevance
“…On the other hand, pre-eclamptic women demonstrated an increased body mass index (BMI), percentage of caesarian section, systolic and diastolic blood pressure, WBC count, serum urea, and uric acid levels as compared to healthy controls. All these data are in accordance with the previous report [19]. Importantly, the glomerular ltration rate (GFR) was found to be signi cantly lower in subjects with PE as compared to healthy pregnant women.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, pre-eclamptic women demonstrated an increased body mass index (BMI), percentage of caesarian section, systolic and diastolic blood pressure, WBC count, serum urea, and uric acid levels as compared to healthy controls. All these data are in accordance with the previous report [19]. Importantly, the glomerular ltration rate (GFR) was found to be signi cantly lower in subjects with PE as compared to healthy pregnant women.…”
Section: Discussionsupporting
confidence: 92%
“…These results are contradictory to an earlier report (Poordast et al 2017) where a signi cantly lower level of this cytokine was demonstrated in pregnant groups (with and without PE) in comparison to healthy non-pregnant subjects. However, in line with our observations, a report by Darmochwal-Kolarz et al (Darmochwal-Kolarz et al 2017) also failed to demonstrate the difference of Il-23A among pregnant subjects with placental insu ciency (fetal growth restriction and PE) and healthy pregnant women. Our result showing a comparable level of IL-23 in subjects with PE and healthy pregnant women matched with the report, as mentioned above.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have shown a significantly higher concentration of IL-17 in the serum of women with a pregnancy complicated by fetal growth restriction (FGR) and preeclampsia, compared to healthy pregnant women. In conjunction with a reduced TGF-β level detected in pregnancy complicated by FGR associated with preeclampsia (PE), it may induce an inflammatory response and, consequently, lead to placental insufficiency [67]. Perhaps the conducted research not only will allow us to understand the role of hormonal balance in the development of autoimmune diseases, but will also open up new opportunities for research on the impact of female sex hormones on the immune system in ovarian cancer [66].…”
mentioning
confidence: 99%